Answer:
(3, - 2 ) and (- 2, 2 )
Explanation:
(8)
2x + y = 4 → (1)
x + 3y = - 3 → (2)
Multiplying (2) by - 2 and adding to (1) will eliminate the x- term
- 2x - 6y = 6 → (3)
Add (1) and (3) term by term to eliminate x
0 - 5y = 10
- 5y = 10 ( divide both sides by - 5 )
y = - 2
Substitute y = - 2 into either of the 2 equations and solve for x
Substituting into (1)
2x - 2 = 4 ( add 2 to both sides )
2x = 6 ( divide both sides by 2 )
x = 3
solution is (3, - 2 )
---------------------------------------------
(9)
3x + 5y = 4 → (1)
x + 3y = 4 → (2)
Multiplying (2) by - 3 and adding to (1) will eliminate the x- term
- 3x - 9y = - 12 → (3)
Add (1) and (3) term by term to eliminate x
0 - 4y = - 8
- 4y = - 8 ( divide both sides by - 4 )
y = 2
Substitute y = 2 into either of the 2 equations and solve for x
Substituting into (2)
x + 3(2) = 4
x + 6 = 4 ( subtract 6 from both sides )
x = - 2
solution is (- 2, 2 )